Imidazolium‐Based Protic Ionic Liquids as Electrolytes for Lithium‐Ion Batteries. Issue 1 (29th November 2018) - Stettner, Timo; Walter, Florian C.; Balducci, Andrea
Abstract: Protic ionic liquids (PILs) have been indicated as a promising class of ionic liquids (ILs) for the realization of high‐performance lithium‐ion batteries (LIBs). In this work we synthesize four different PILs containing the imidazolium‐based cations 1, 2‐Dimethylimidazolium (1, 2‐DMim + ) and 1‐Methylimidazolium (1‐Mim + ), and the anions bis(trifluoromethanesulfonyl)imide (TFSI − ) and bis(fluorosulfonyl)imide (FSI − ). We show that these PILs display good conductivities and low viscosities and that they can be successfully used in combination with lithium iron phosphate (LFP) electrodes. Among the investigated electrolytes, 0.5 M LiTFSI in 1, 2‐DMImTFSI appears as the most promising candidate for the realization of systems with high capacity retentions at high C‐rates and high cycling stabilities. Abstract : Going without solvent : protic ionic liquids display all the favourable properties of ionic liquids, but they are easier and cheaper to synthesise compared to their aprotic counterparts. In this study, the influence of the combination of anion and cation on the properties of protic ionic liquids is investigated. Furthermore, it is shown that protic ionic liquids are very promising electrolytes for lithium‐ion batteries.